Impact of fermented whey addition on resulting sensory characteristics and consumer preference of ripened cheeses - Ramos-Gabriel, Saris Ulises; Corredor, José Andrés Herrera-; Alvarado, José Guadalupe Gamboa-; Rivera, Emmanuel de Jesús Ramírez- (Emirates Journal of Food and Agriculture, 2019)
The objective of this research was to evaluate the impact of fermented whey on the sensory characteristics of ripened cheeses and consumer preference. Ripened cheeses from 24, 25, 26, 27 and 28 months were characterized. The sensory techniques used were: Quantitative Descriptive Analysis®, Temporal Dominance of Sensations and External Preference Mapping. The results showed that the ripened cheeses of 24 to 27 months they were characterized by white color, acidified milk smell, fat aroma and acidified cream smell. The cheese of 28 months of ripened was perceived as fermented milk smell, cow smell and fat smell. The dominant attributes were fat aroma, bitter aftertaste, acid aftertaste and salty. Consumers preferred cheeses from 26 and 27 months of ripening. These results demonstrate the potential use of fermented whey as an alternative to produce ripened cheeses with sensory characteristics and their relation to consumer preference.